EXAMINATION ON THE MODIFICATION OF THE VESSELS WITHIN THE ANNUAL RING IN SEVERAL SPECIES OF THE GENUS OAK (G. QUERCUS) - Bardarov, Nicolay; Nistorova, Rumena (Innovation in Woodworking Industry and Engineering design, 2012)
The construction of the ring porous wood species strongly depends on there width of the rings. It has most changing in the size and the location of the vessels. The work examines one of the main representatives of ring porous wood - genus Oak.It was examined several species of the genus, and it was measured diameter and density of the vessels. It was examined the change of these anatomical features within the annual ring. Made a comparison between values to determine their impact on the use of wood.